2014
DOI: 10.1103/physrevb.90.094102
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of the high-temperature phase transformation in yttrium tantalate

Abstract: The high temperature phase transition between the tetragonal (scheelite) and monoclinic (fergusonite) forms of yttrium tantalite (YTaO 4 ) has been studied using a combination of firstprinciples calculations and a Landau free-energy expansion. Calculations of the Gibbs free energies show that the monoclinic phase is stable at room temperature and transforms to the tetragonal phase at 1430 o C, close to the experimental value of 1426 ± 7 o C. Analysis of the phonon modes as a function of temperature indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
62
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 49 publications
7
62
2
2
Order By: Relevance
“…In special high-pressure (HP) studies of MTO 4 ternary oxides have generated a large amount of attention, with HP being an efficient tool in improving the understanding of their physical properties [3][4][5][6][7][8][9][10][11][12]. Recently, other compounds such as perrhenates [17] and orthotantalates [18] have also become the focus of research. One material of particular interest is indium tantalate (InTaO 4 ), a promising candidate as an efficient photocatalytic for water splitting, which is a potential source of green energy [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In special high-pressure (HP) studies of MTO 4 ternary oxides have generated a large amount of attention, with HP being an efficient tool in improving the understanding of their physical properties [3][4][5][6][7][8][9][10][11][12]. Recently, other compounds such as perrhenates [17] and orthotantalates [18] have also become the focus of research. One material of particular interest is indium tantalate (InTaO 4 ), a promising candidate as an efficient photocatalytic for water splitting, which is a potential source of green energy [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover both theoretical and experimental results reveal that YTaO 4 ceramic exists ferroelastic transformation with almost no volume difference, and the ferroelastic transformation of YTaO 4 ceramic may lead to high fracture toughness similar to YSZ. 16 In the previous work, we 17 synthesized RETaO 4 (RE = Y, La, Nd, Sm, Gd, Dy, Yb) ceramics with similar properties to YTaO 4 by solid-state reaction, and verified its potential as TBC application.…”
Section: Introductionmentioning
confidence: 78%
“…On cooling, the T phase goes through a displacive transformation to form the M phase instead of the M' phase; this process is also referred to as a ferroelastic transformation and occurs with almost no volume change. The high-temperature phase transition between the tetragonal and monoclinic forms of YTaO 4 has been studied using a combination of first-principles calculations and a Landau free-energy expansion by Feng et al [19]. Wang et al [20] investigated the thermal properties of RETaO 4 (RE=Nd, Eu, Gd, Dy, Er, Yb, Lu) and found that the RETaO 4 ceramics have lower thermal conductivities than that of YSZ.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with that of the standard XRD spectra of defect-fluorite SmTaO 4 (JCPDS data card: 24-1010), the phase structure of SmTaO 4 ceramics are a monoclinic phase (space group: I2 (5)) with no evidence of impurity. The Ta atom coordinates with four O atoms to form a TaO 4 tetrahedron, and the samarium ion and TaO 4 tetrahedron form a structure with a coordination number less than eight[19]. The XRD patterns of Sm 3 TaO 7 ceramics are in agreement with the standard XRD spectrum (JCPDS data card: 36-0672), suggesting that the phase structure of Sm 3 TaOThe XRD results demonstrate that the crystal structures of Sm 3 TaO 7 and SmTa 3 O 9 are more complex than that of SmTaO 4 , which can be explained according to the Clarke model[15]: TaO 7 and SmTa 3 O 9 consist of high atomic masses and complex crystal structures, which means that Sm 3 TaO 7 and SmTa 3 O 9 have lower thermal conductivity[32].…”
mentioning
confidence: 99%